Comportamento de genótipos de alface com o alelo mo10 ao Lettuce mosaic virus e Lettuce mottle virus - Suzuki, Gerson Shinya [UNESP] (2014)
Lettuce (Lactuca sativa L.) belongs to the Asteraceae family and is one of the most consumed vegetables in Brazil. One of the major disease problems in this crop are plant viruses, especially the Lettuce mosaic virus (LMV) that cause losses to producers in various regions of the country, but also Lettuce mottle virus (LeMoV). As a form of control, the use of resistant varieties is the most effective way to overcome the damage caused by plant viruses. Most of the resistant varieties of lettuce makes the use of recessive genes, mostly involved in plant-virus interactions and characterized as eukaryotic translation initiation factor (eIFs). Thus, this study aimed to evaluate two lettuce genotypes (169501 and 169501C) for resistance to LMV and LeMoV. LMV and LeMoV were sap transmitted at different time of intervals. For LMV also transmissions with aphids were carried out. The two varieties tested were resistant to LMV in both forms of transmission, but showed symptoms when inoculated with LeMoV. In RT-PCR with specific primers, LMV was not detected but LeMoV yes, confirming the infection in the inoculated plants. The isolate of LMV used in the tests was not classified as belonging to subgroups Most ...